Trace Minerals and Heavy Metals: Implications in Prostate Cancer (Bangladesh Journal of Medical Biochemistry, 2017)
Dietary minerals and environmental heavy metals are modifiable factors that have been studied over the years for associations with prostate cancer risk. This review consideres the recent evidence in this field and concludes that the role of dietary minerals and environmental elements in prostate cancer progression or prevention is not yet clear and further research is needed to elaborate on the current knowledge.Bangladesh J Med Biochem 2015; 8(1): 27-32